Genetic and environmental regulation of plant architectural traits and opportunities for pest control in raspberry - Graham, J.; Hackett, C.A.; Smith, K.; Karley, A.J.; Mitchell, C.; Roberts, H.; O'Neill, T. (Annals of applied biology, 2014)
Part of the reason for the under‐exploitation of physical resistance traits in plant breeding is that the genetic basis and heritability of these traits is poorly characterised, and any associations of particular traits with pest and disease resistances have yet to be determined. In raspberry, some associations between architectural traits and disease resistances have been demonstrated, for example cane hairs and resistance to cane diseases. The aim of this work is to examine a range of traits, including leaf trichomes, leaf density, cane density, bush density, lateral length and lateral numbers, to determine the heritability and therefore breeding potential of these traits. The effect of these traits against aphids and spider mites, two important pests in raspberry, was examined. Chromosomal regions with candidate genes regulating these traits were identified as the first step to understanding the genetic control.